p37mos-associated serine/threonine protein kinase activity correlates with the cellular transformation function of v-mos. - Singh, B (1986)
A serine/threonine-specific protein kinase activity is closely associated with v-mos-encoded proteins. Experiments were conducted with several mutant forms of p37mos to determine whether or not the kinase function correlates with the biological activity of the mutant v-mos genes. Two mutants lacking cell transformation activity, one an arginine substitution for lysine-121 in the putative ATP-binding site and the other a 23-amino acid deletion from the C-terminal end of p37mos, had no kinase activity associated with their mutant proteins. However, a third mutant with reduced biological activity had drastically less kinase activity than the wild-type protein. The latter mutant was able to phosphorylate the kinase-inactive p37mos(Arg-121) protein in vitro. These results indicate that even though p37mos(Arg-121) can be phosphorylated in trans by other kinase molecules, it lacks the ability to phosphorylate itself in vitro. This provides a compelling argument that the protein kinase function of p37mos is an intrinsic property of the protein. Moreover, since the kinase function correlates with the cellular transformation activity of the v-mos gene, we predict that it is required for the biological activity of the v-mos gene.